Um "outro" de muitas faces : islamofobia e articulações de ódio entre o Brasil e o mundo - Igor Gonçalves Caixeta (2023)
Based on the conceptualization of Islamophobia as a global hate speech, this dissertation has as its central goal to establish an international and national political panorama of Islamophobia, from its first expressions to the present day. It seeks to present some of the actors and structures of thought responsible for globalizing Islamophobic discourses, locating them in their historical contexts, and theorizing about the ways and reasons why they are articulated. It demonstrates that Islamophobia is an ancient, multifaceted and globally widespread phenomenon, which allows for the most diverse appropriations in different parts of the world. In Brazil, despite being a marginal type of hatred compared to other forms of stereotyping and subalternization, Islamophobia can be observed since colonization. In line with other countries, Islamophobia was cultivated throughout Brazilian history by multiple movements, through different ideologies, such as colonialism, racism, religious nationalism, liberalism and fascism, which arrived in waves of globalization. Understanding the "Other", a condition attributed to Muslims globally, as a sign to which new words can always be incorporated, the dissertation proposes the analysis of the symbolic links made between different otherized groups. This discursive practice, named "articulation of hatred", is characterized as a political tool that contributes to the construction of hierarchies and the destruction of solidarities.